Classifying biogeographic realms of the endemic fauna in the Afro‐Arabian region - Soultan, Alaaeldin; Wikelski, Martin; Safi, Kamran (Ecology and evolution, 2020)
Aim Understanding diversity patterns and identifying the environmental factors that shape these patterns are essential for ecology and conservation. The Afro‐Arabian region comprises one of the most important biogeographic areas connecting continents. Yet, little emphasis has been put on understanding its endemic fauna in relation to its biogeographic realms. Our objective is to fill the gaps in knowledge on diversity patterns and biogeography that are essential for prioritizing the overdue conservation efforts. Location The study area covers mostly the hot desert climate region in North Africa and Arabia, and includes the Mediterranean, Sahel, and Ethiopian highlands (hereafter “Afro‐Arabian region”). Methods We used distribution maps developed by IUCN and BirdLife for species endemic to the Afro‐Arabian region belonging to the four tetrapod classes, amphibians, reptiles, birds, and mammals, to identify the endemic richness hotspots. We then used multivariate analyses to delineate biogeographic regions and evaluate their relationship with the environmental factors. Results Our study reveals a complex map of the richness hotspots for the endemic tetrapod classes. The main hotspots of endemism were concentrated at the margins of the study area, along the Mediterranean coast, Ethiopian highlands, and along the Red Sea Mountains. We propose classifying the Afro‐Arabian region into three discrete biogeographic realms for endemic amphibians, four for reptiles and birds, and five discrete biogeographic realms for endemic mammals. The identified realms are defined by their environmental conditions and the historical geological processes. Main conclusions Richness hotspots of endemic tetrapod classes were heterogeneously distributed in the Afro‐Arabian region. Our results support the hypothesis that species diversity patterns and endemism have been shaped by the environmental conditions and the paleogeographic processes. Each of the identified bioregions is associated with a characteristic set of tetrapod species. Our results are a benchmark for assessing the effectiveness of the protected areas and for implementing conservation plans for biodiversity. Although the Afro‐Arabian region comprises one of the most important biogeographic areas connecting continents, little emphasis has been paid to understand the classification of its endemic fauna into biogeographic realms. Here, we fill the gaps in knowledge on diversity patterns and biogeography essential for prioritizing conservation efforts that are overdue. We propose classifying the Afro‐Arabian region into three discrete biogeographic realms for endemic amphibian, four for reptiles and birds, and five discrete biogeographic realms for endemic mammals.